Development of HCV genotyping protocol based on high resolution melting analysis real-time PCR: a pilot study - Hamzah, Hairul Aini (2017)
Determination of HCV genotype is important for the disease prognosis and prediction of treatment outcomes. Several methods of genotyping are commercially available and others are done in-house. Aims for the study were to elucidate nucleotide sequence of local HCV strains and to establish an in-house technique for HCV genotyping using DNA intercalating dye real-time PCR. HCV RNA was extracted and subjected to reverse transcription before amplification using SsoFast EvaGreen mix real-time PCR. Sequence analysis of the 5’UTR revealed two major groups of HCV genotypes (1 and 3). The GC content HCV genotype 1 and 3 were 57.14-58.44% and 55.19-57.14, respectively. HCV RNA was able to be detected with the PCR mix reaction. However, both main genotypes are indiscriminately clustered using high resolution melting analysis and melting temperature analysis. Further modification of the established method could result in better outcomes.